Perancangan Website UMKM Pekanbarushoppingmall Menggunakan Visual Studio Code Untuk Pemasaran dan Promosi Pekanbarushoppingmall - Adinda Wafiq Zahira; Astrid, Astrid; Jordhi Yuza Pratama (CV. ITTC INDONESIA, 2024)
This article aims to design a website for Pekanbarushoppingmall MSMEs using Visual Studio Code as a tool to improve marketing and promotion of cosmetics, accessories and buckets. The method used includes data collection through interviews with the owner and direct observation at the Pekanbarushoppingmall shop, followed by designing the database, appearance and structure of the website http://pekanbarushoppingmall.rf.gd/index.html. This design shows that the website developed functions as an effective digital storefront, provides complete information about products, and facilitates interaction with consumers. The conclusion of this project states that the implementation of this website is expected to increase the existence of Pekanbarushoppingmall in the market